Nitretação por EDM do Aço AISI 4140 - Santos, Rogério Felício dos (2013)
The objective of this study was to investigate the nitriding possibility on AISI 4140 steel samples, through the electrical discharge machining (EDM) process. The tests were executed on die sinking EDM machine, with some adaptations. As dielectric fluid, it was used a deionized water and urea solution. As electrode tool it was used electrolytic copper. The characterization techniques used were the micrographic analysis, x-ray diffraction, laser interferometry, GDOES, nanoindentation and microhardness. The electrical discharges were photographed using high speed camera. The results showed the formation of a rich nitride layer with a thickness between 20 and 25 micrometers. A decay occurs in the concentration from the surface. There was a gain in hardness, but it was not detected any change in the elasticity modulus. The electrical discharges photographs revealed the interference of urea on the same, however there was no significant topography alteration. The proposed model for nitriding is based on the nitrogen insertion on the steel surface by ion implantation. Thus, it can be concluded that the use of electric discharges showed a viable method of nitriding. The technological potential of the process was explored with complementary studies.